Risk Aversion and Prudence in Contests - Marco Sahm (Center for Economic Studies and ifo Institute (CESifo), 2017)
I examine the impact of risk preferences on efforts and winning probabilities in generalised Tullock contests between two players. The theoretical analysis yields two main results. First, I specify a sufficient condition on the agents' comparative prudence under which a higher common level of risk aversion leads to lower aggregate effort in symmetric contests. Second, I show that for a certain range of parameters in asymmetric contests, higher risk-aversion will be a disadvantage if the agent is comparatively prudent.
Keywords: C72; D72; 330; Tullock contest; risk aversion; prudence